Critical Digital Art History : Interface and Data Politics in the Post-Digital Era (Intellect Books, 2024)
Digital Art History has often aligned itself with the practical concerns of digital technology and the responsibilities of art institutions and associated institutional roles such as collection managers, information specialists, curators, and conservators. This emphasis on practicalities and implementation, while undeniably important, has often meant that there is little room for critical examination of the broader implications of digital technology and computational methodologies in art history. This anthology seeks to address the dearth of critical reflection by approaching the use of digital technology in art history from a theoretical perspective and critically assessing specific case study examples. This book also considers the political dimensions associated with the large-scale digitization and the application of digital tools within museums and collection management. A long-standing concern of the field—and also a major focal point of this book—is museum and collecting practices in the digital era. While there is a certain degree of continuity in the field, there are some important shifts and changes too. One of the key changes is the widespread uptake of artificial intelligence tools and an increased attention to both the broader historical and societal aspects of the use of digital tools within museums and collection management.